2010
DOI: 10.1590/s1516-44462010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Anormalidades cognitivas no uso da cannabis

Abstract: Objective: Evidence that cannabis use impairs cognitive function in humans has been accumulating in recent decades. The purpose of this overview is to update knowledge in this area with new findings from the most recent literature. Method: Literature searches were conducted using the Web of Science database up to February 2010. The terms searched were: "cannabi*" or "marijuana", and "cogniti*" or "memory" or "attention" or "executive function", and human studies were reviewed preferentially over the animal lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 123 publications
0
22
0
3
Order By: Relevance
“…In addition to findings that suggest alterations in neurocognitive function (Pope and Yurgelun-Todd 1996; Harvey et al 2007; McHale and Hunt 2008; Solowij and Pesa 2010; Gruber et al 2011a; Lisdahl and Price 2012) and inhibitory processing (Gruber and Yurgelun-Todd 2005; Tapert et al 2007; Schweinsburg et al 2008; Jacobus et al 2009a; Gruber et al 2012a) in chronic MJ smokers relative to control participants, several investigations have also reported alterations in frontal white matter microstructure, measured with diffusion tensor imaging (DTI) techniques in adult MJ smokers (Arnone et al 2008; Ashtari et al 2009; Bava et al 2009; Jacobus et al 2009b; Gruber et al 2011b). Arnone et al (2008) reported increased mean diffusivity (MD)/trace in the prefrontal area of the corpus callosum in MJ relative to controls; this trended towards a positive correlation between diffusivity levels and length of use.…”
Section: Introductionmentioning
confidence: 90%
“…In addition to findings that suggest alterations in neurocognitive function (Pope and Yurgelun-Todd 1996; Harvey et al 2007; McHale and Hunt 2008; Solowij and Pesa 2010; Gruber et al 2011a; Lisdahl and Price 2012) and inhibitory processing (Gruber and Yurgelun-Todd 2005; Tapert et al 2007; Schweinsburg et al 2008; Jacobus et al 2009a; Gruber et al 2012a) in chronic MJ smokers relative to control participants, several investigations have also reported alterations in frontal white matter microstructure, measured with diffusion tensor imaging (DTI) techniques in adult MJ smokers (Arnone et al 2008; Ashtari et al 2009; Bava et al 2009; Jacobus et al 2009b; Gruber et al 2011b). Arnone et al (2008) reported increased mean diffusivity (MD)/trace in the prefrontal area of the corpus callosum in MJ relative to controls; this trended towards a positive correlation between diffusivity levels and length of use.…”
Section: Introductionmentioning
confidence: 90%
“…Fourth, we queried third-party informants to test the "everyday cognition" hypothesis that cannabis-induced neuropsychological impairment translates into functional problems in daily life. Fifth, we tested the "developmental vulnerability" hypothesis that individuals who begin cannabis use as adolescents are particularly vulnerable to the effects of persistent cannabis use on neuropsychological functioning, as evidence suggests that cannabis has especially toxic effects on the developing brain (24)(25)(26)(27)(28)(29)(30)(31). Sixth, we tested the "recovery" hypothesis that former persistent users who quit or reduce their cannabis use may be able to restore their neuropsychological health.…”
mentioning
confidence: 99%
“…Por ser a droga ilícita mais usada no mundo, o estudo de tais déficits é de extrema importância. 1 De forma sumária, os autores sugerem que o uso crônico da cannabis causa alterações que podem ser persistentes, mesmo após a cessação do uso, em diversas funções cognitivas. Estes efeitos seriam ainda piores em usuários pesados e com início do uso na adolescência.…”
Section: Qual a Verdadeira Associação Entre Disfunção Cognitiva E O Uunclassified
“…Estes efeitos seriam ainda piores em usuários pesados e com início do uso na adolescência. 1 A partir destes dados, temos algumas ressalvas a fazer. Uma variável que não é avaliada em nenhum estudo e que pode confundir os achados trata-se das disfunções cognitivas pregressas ao uso da droga, resultando na busca e experimento da mesma.…”
Section: Qual a Verdadeira Associação Entre Disfunção Cognitiva E O Uunclassified